TEI Lex-0 In Action: Improving the Encoding of the Dictionary of the Academia das Ciências de Lisboa - Salgado, Ana (2019)
This paper describes some experiments made while encoding the first complete dictionary of the Academia das Ciências de Lisboa (DACL) in the context of TEI Lex-0, a community-based interchange format for lexical data aimed at facilitating the interoperability and reusability of lexical resources. Even though the original encoding of the DACL was based on TEI, we decided to switch to TEI Lex-0 because it allowed us to streamline our encoding. Our experiments show that even though TEI Lex-0 is stricter than TEI itself (allowing fewer elements and imposing certain constraints that are not present in plain TEI), it is fully capable of representing the complexities of the entry structure of the DACL. In the paper, we discuss the TEI Lex-0 encoding of the DACL, as well as the conversion methodology and the tools used for the automatic conversion from the original encoding. We are currently focusing on the macrostructural level, more precisely on the types of lexical units and on the written and spoken forms of the lemma, providing a set of modelling principles and representation forms of every type of entry in the DACL. This paper is part of ongoing work and a contribution to the efforts of the DARIAH-ERIC Lexical Resources working group.